ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL POKOK BAHASAN OPERASI HITUNG PECAHAN DI SMP NEGERI 13 PONTIANAK - Uun Walyanda; Halini Halini; Ahmad Yani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThis case study research aims to ind out what are the difficuties experienced by students in solving the problem of fractional counting operations in SMP Negeri 13 Pontianak. The research method sed in this research is descriptive mhetod. Data collection tool used in this research is essay test in the form of diagnostic test and interview. Subject of the study amounted to four student, four student were selected based on the number of mistakes made in solving problems that have been given. Based on analysis difficulties experienced by students in the form of diffculty using the concept and difficulty using the principle. The results showed that there are many student who have difficulty, difficulty using the concept of difficulties in the concept of summing the fractions of value, the reduction of the denominations and the concept of equalizing the denominator of two fractions using the KPK. While the difficulty of using the principle of difficulties in the principle of addition of two fraction, the principle of reduction of two fractions and the principle of simplification of fractional operations.Keywords: Analysis of Difficulties, Solving Problems, Concept Difficulties and Principle